Dialogue of Prose and Poetry in the Works of Doris Lessing (the novel “Alfred and Emily” and the poetic sequence “The Fourteen Poems”) - Proskurina, Nataliia; Kravets, Olena (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
The article is dedicated to the work of the contemporary English writer, Nobel laureate Doris Lessing. The object of the analysis is the artist`s last novel «Alfred and Emily» (2008) and the poetic sequence «The Fourteen Poems» (1959), in which a deep motivic relationship was revealed. It was found that the motif of memory is a crucial one in author’s works, and the motifs that correlate with it (in particular, war catastrophe, childhood, oblivion, and guilt) create a common associative field. Lessing`s last novel, which thematically fits into the discourse of texts about the First World War, reveals the features of an autofictional text. The author organically combines documentary and fiction in the work, creating a personal history of the beginning of the 20th century. The writer resorts to an alternative development of history: excludes the event traumatic for humanity (the First World War) from the novel, so the story acquires features of subjectivity. The second part of the work, a documentary, dissonates with the first, revealing the tragic consequences of the Great War. D.Lessing tries to comprehend the nature of war as a catastrophe through the traumatic experience of several generations. The novel events are connected with the fate of D. Lessing`s parents – Alfred and Emily, whose names are mentioned in the novel`s title. The fictional and documentary parts of the work have symbolic subtitles («Alfred and Emily: a novella», «Alfred and Emily; two lives»). The paratextual elements of the text perform several functions: suggestive (title; epigraph – lines from the novel by D. H. Lawrence «Lady Chatterley`s Lover»), reflexive (preface and author`s comments; encyclopedic article), visual (photographs from the family archive). It is proved that the poetic sequence «The Fourteen Poems» can be considered from the point of view of intertextuality as an autocontext to the novel «Alfred and Emily». The leitmotif of memory visualizes the meaningful connection between the novel «Alfred and Emily» and the poetic sequence. Both the lyrical heroine and the characters of the novel are immersed in their memories and demonstrate the existential vulnerability of the individual to the catastrophe of war. For the characters, their childhood symbolizes a safe and cozy world – home, but it is also marked by parental experience and permeated by war.